Dynamic Response Analysis of Cable of Submerged Floating Tunnel under Hydrodynamic Force and Earthquake - Zhiwen Wu; Guoxiong Mei (Shock and Vibration)
A simplified analysis model of cable for submerged floating tunnel subjected to parametrically excited vibrations in the ocean environment is proposed in this investigation. The equation of motion of the cable is obtained by a mathematical method utilizing the Euler beam theory and the Galerkin method. The hydrodynamic force induced by earthquake excitations is formulated to simulate real seaquake conditions. The random earthquake excitation in the time domain is formulated by the stochastic phase spectrum method. An analytical model for analyzing the cable for submerged floating tunnel subjected to combined hydrodynamic forces and earthquake excitations is then developed. The sensitivity of key parameters including the hydrodynamic, earthquake, and structural parameters on the dynamic response of the cable is investigated and discussed. The present model enables a preliminary examination of the hydrodynamic and seismic behavior of cable for submerged floating tunnel and can provide valuable recommendations for use in design and operation of anchor systems for submerged floating tunnel.